2012
DOI: 10.1007/s11906-012-0305-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria, Myocardial Remodeling, and Cardiovascular Disease

Abstract: The process of muscle remodeling lies at the core of most cardiovascular diseases. Cardiac adaptation to pressure or volume overload is associated with a complex molecular change in cardiomyocytes which leads to anatomic remodeling of the heart muscle. Although adaptive at its beginnings, the sustained cardiac hypertrophic remodeling almost unavoidably ends in progressive muscle dysfunction, heart failure and ultimately death. One of the features of cardiac remodeling is a progressive impairment in mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 73 publications
1
39
0
Order By: Relevance
“…In contrast, proteins like dynamin-related protein-1 (Drp1) and fission protein-1 (Fis1) controlling mitochondrial fission. 18 In type 2 diabetic patients, smaller mitochondria has been found, and mitochondrial fusion protein levels were decreased. 19,20 In skeletal muscle, mitochondrial fusion protein modulates insulin signal pathway and glucose homeostasis via regulating mitochondrial function also have been reported.…”
Section: Mitochondria Play Critical Roles In Energy Production and Mementioning
confidence: 99%
“…In contrast, proteins like dynamin-related protein-1 (Drp1) and fission protein-1 (Fis1) controlling mitochondrial fission. 18 In type 2 diabetic patients, smaller mitochondria has been found, and mitochondrial fusion protein levels were decreased. 19,20 In skeletal muscle, mitochondrial fusion protein modulates insulin signal pathway and glucose homeostasis via regulating mitochondrial function also have been reported.…”
Section: Mitochondria Play Critical Roles In Energy Production and Mementioning
confidence: 99%
“…In cardiac disease, as seen in heart failure, the cytosolic and mitochondrial ROS become distorted, leading to oxidative imbalance, mitochondrial dysfunction and eventually to cell death [4]. It has been demonstrated that the more the cardiac function in this patient group is impaired, the more signs of apoptosis and oxidative stress appear [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of ROS may be protective (7,23) and affect signaling pathways that may stimulate growth (5). However, an imbalance between ROS production and the normal cellular antioxidant defense system will lead to oxidative stress and potentially in DNA damage (10).…”
mentioning
confidence: 99%